Identification of Silkworm Hemocyte Subsets and Analysis of Their Response to Baculovirus Infection Based on Single-Cell RNA Sequencing - Feng, Min; Xia, Junming; Fei, Shigang; Peng, Ruoxuan; Wang, Xiong; Zhou, Yaohong; Wang, Pengwei; Swevers, Luc; Sun, Jingchen (Frontiers in Immunology, 2021)
A wide range of hemocyte types exist in insects but a full definition of the different subclasses is not yet established. The current knowledge of the classification of silkworm hemocytes mainly comes from morphology rather than specific markers, so our understanding of the detailed classification, hemocyte lineage and functions of silkworm hemocytes is very incomplete. Bombyx mori nucleopolyhedrovirus (BmNPV) is a representative member of the baculoviruses and a major pathogen that specifically infects silkworms (Bombyx mori) and causes serious losses in sericulture industry. Here, we performed single-cell RNA sequencing (scRNA-seq) of hemocytes in BmNPV and mock-infected larvae to comprehensively identify silkworm hemocyte subsets and determined specific molecular and cellular characteristics in each hemocyte subset before and after viral infection. A total of 20 cell clusters and their potential marker genes were identified in silkworm hemocytes. All of the hemocyte clusters were infected by BmNPV at 3 days after inoculation. Interestingly, BmNPV infection can cause great changes in the distribution of hemocyte types. The cells appearing in the infection group mainly belong to prohemocytes (PR), while plasmatocytes (PL) and granulocytes (GR) are very much reduced. Furthermore, we found that BmNPV infection suppresses the RNA interference (RNAi) and immune response in the major hemocyte types. In summary, our results revealed the diversity of silkworm hemocytes and provided a rich resource of gene expression profiles for a systems-level understanding of their functions in the uninfected condition and as a response to BmNPV.